Pesantren Strategy in Building the Character of Millennial Participants in the 5.0 Era - Yusutria; Yazida Ichsan; Hanafiah, Yusuf; Charles (BiCED Proceeding, 2023)
The poor socio-cultural conditions of the surrounding community manifest the weakness of social institutions in controlling social change, which negatively impacts character decline. Communication ethics and a critical attitude are also essential to develop the character of the millennial generation, especially students in Islamic boarding schools, who foster, guide, shape, and instill the morals of students in seeking knowledge. Santri must be able to keep up with increasingly modern developments to stay caught up in action. Therefore, the right strategy is needed. The research aims to determine the Islamic boarding school's approach to developing the personality of the millennial generation at the Modren Baitussalam Prambanan era 5.0 Islamic boarding school. This descriptive and qualitative research uses observation, interview, and documentation techniques. Data analysis starts with visualizing all the data, reducing the data, and concluding. The result is the need for an understanding of students' cultural differences and personalities, good role models, and awareness of technological and information advances for students so they don't miss out and instilling a pancajiwa culture in Islamic boarding schools. The obstacles come from the student's personality.